Analytical formula of European-style power call options in an MFBM with jumps model - Ibrahim, Siti Nur Iqmal; Kilicman, Adem; Laham, Mohamed Faris (RMP Publications, 2022)
Studies have shown that stock price process exhibits long-range dependence. To address this, many have introduced the mixed-fractional Brownian motion (MFBM) model to the stock price process. Under risk-neutral measure, this study provides an analytical formula for the price of European-style power call options in an MFBM environment with the inclusion of the jumps process. Modeling the stock price with MFBM and jumps process enables the capturing of long memory trend as well as discontinuity in the stock price process.